Association of rs11209032 and rs1004819 Polymorphisms in Interleukin-23 Receptor Gene With Ankylosing Spondylitis - Müjgan ÖZDEMİR ERDOĞAN and Tuğba Şule ÇANKAYA and Alper Murat ULAŞLI and Saliha Handan YILDIZ and Evrim Suna ARIKAN TERZİ and Tuba ÇAVDAR and Ümit DÜNDAR and Mustafa SOLAK (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the distribution of human leukocyte antigen B27 (HLA-B27) alleles (+/-) and interleukin-23 receptor (IL-23R) gene rs11209032 and rs1004819 polymorphisms among ankylosing spondylitis (AS) patients in a Turkish cohort. Patients and methods: The study sample comprised 106 AS patients (89 males, 18 females; mean age 38.9±10 years; range 19 to 65 years) and 82 healthy controls (70 males, 12 females; mean age 32.15±7.07 years; range 19 to 51 years). Distribution of HLA-B27 alleles (+)/(-) in AS patients were observed by reverse hybridization technique. Genotyping of IL-23R rs11209032 and rs1004819 polymorphisms of AS patients and healthy controls were performed by real time polymerase chain reaction. Results: Of the AS patients, 69 (65.1%) were HLA-B27 positive. Distribution of rs11209032 genotype frequencies in AS group were 31.1% for GG, 50.9% for GA, and 17.9% for AA; while in control group, it was 34.1% for GG, 53.7% for GA, and 12.2% for AA. Distribution of rs1004819 genotype frequencies in AS group were 30.2% for CC, 52.8% for CT, and 17.0% for TT; while in control group, it was 42.7% for CC, 46.3% for CT, and 11.0% for TT. There was no significant difference between AS patients and controls in terms of genotype frequencies of IL-23R gene rs11209032 and rs1004819 polymorphisms. Conclusion: No association was found between AS and IL23R rs11209032 and rs1004819 polymorphisms in this Turkish AS cohort.